Computer algorithms introdiction to design and analysis - Baase, Sara (Addison-Wesley series in computer science., 1988)
This second edition offers an unusually thorough and readable look at the design and analysis of algorithms, including an exhaustive array of algorithms and their complexity analyses.Baase emphasizes the development of algorithms through a step-by-step process, rather than merely presenting the end result. Three chapters on modern topics are new to this edition: adversary arguments and selection, dynamic programming, and parallel algorithms.